ANALISIS KETERLAKSANAAN KURIKULUM 2013 DITINJAU DARI STANDAR PROSES DI KELAS XI MIPA 2 DI SMA NEGERI 1 KOTA PEKANBARU - Fatimah, Siti; Darmawati, Darmawati; Suryawati, Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Research has been conducted in Pekanbaru 1 Public High School in January-February 2018 which aims to find out the implementation of the 2013 curriculum in terms of the standard processes in Class XI MIPA 2 in SMA Negeri 1 Pekanbaru City using purposive sampling technique. The sample used in this study were students of class XI MIPA 2 and 1 biology teacher in class XI MIPA 2. The instruments used were assessment sheets and observation sheets. Furthermore, the assessment sheet is used to assess the learning tools and assessment of learning outcomes, while the observation sheet is used to see the learning process. Based on the results of the study it can be concluded that the implementation of the 2013 curriculum in terms of the standard process there are three stages: the planning stage includes a syllabus obtaining an average score of 75% with good criteria, RPP with an average score of 88.7% with very good criteria. For the implementation phase, it obtained an average value of 2.9 with good criteria. While the assessment of learning outcomes with an average score of 75% is classified as good criteria.Key Words: Analysis, Curicullum 2013, Standard Process